Comparative Analysis Of The Financial Performance Of Pt. Sarana Tower Nusantara Tbk (Towr) With Pt. Telekomunikasi Indonesia Tbk For The Period 2021-2022 - Iin Widiyastuti; Fransisca Tuti Rahayu; Pidha Tri Rahayu (Nomico, 2024)
This study aims to determine the financial condition of two companies by calculating the comparative analysis of the financial statements of PT Sarana Menara Nusantara Tbk with PT Telekomunikasi Indonesia Tbk using the calculation of financial ratios. The ratios used are liquidity ratio, solvency ratio, profitability ratio, activity ratio, and market ratio. This research is a comparative research using literature study. The type of data in this study is secondary data, namely the company's financial statements for the 2021-2022 period. Data analysis is carried out using predetermined formulas for each ratio. The results showed that the liquidity ratio, activity ratio, solvency ratio, profitability ratio, and market ratio of PT Telekomunikasi Indonesia Tbk were superior to PT Sarana Menara Nusantara Tbk. This finding indicates that PT Telekomunikasi Indonesia Tbk has better overall financial performance during the period. This study provides important insights for investors and company management in making strategic decisions based on comprehensive financial ratio analysis. In addition, this study emphasizes the importance of periodic evaluation of financial performance to identify the strengths and weaknesses of the company.